Design Short Movie “Nggabrul” as a Theraupeutic Medium for Children Post Covid-19 Pandemic - Philipus Nugroho Hari Wibowo; Elara Karla N; Surya Farid S (Capture : Jurnal Seni Media Rekam, 2023)
This study discusses the design of a short film titled Nggabrul as one of the media used as therapy for primary school children. The COVID-19 pandemic has caused parents to worry about their children's education and eventually help them do their homework. The purpose of this design is to produce a film with a cinematic therapy approach by taking the theme of current life phenomena. Cinema therapy can be said to be the use of movies or watching activities to manage medical health, mental health, and life management. The design method used refers to the stages of creative design proposed by Graham Wallas, consisting of (a) preparation, (b) incubation, (c) illumination, and (d) verification. The result is a simple storytelling package. With the choice of angles of the online learning process in the era of COVID-19 as well as the proper cinematographic techniques, the Nggabrul film becomes one of the right therapeutic media for children to face the new normal era and provide moral teachings of honesty. The results of this design are expected to inspire the filmmaker to produce films that respond to the latest phenomena in society. Keywords: short movie, Nggabrul, cinema therapy, COVID-19 pandemic, Graham Wallas